INDIVIDUAL COMPANY THROUGH CREATION OF WORK IN FACING THE ERA OF INDUSTRY 4.0 - Santi Diansari (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
Companies that fulfill micro and small businesses can be companies founded by two people or by one person in the form of an individual company with a capital whose amount is determined by the decision of the founder of the company as stipulated in Government Regulation Number 8 of 2021. The problem in this research is how is the harmonization of company legal arrangements that can provide legal protection to individual companies? And how is the legal arrangement of individual companies in the future in order to guarantee legal certainty. The research method used in this research is normative juridical research with descriptive analytical research. The data used is secondary data, while the data analysis technique uses deductive or deductive methods. The results of the study indicate that the harmonization of company legal arrangements that can provide legal protection to individual companies in this case is Law Number 40 of 2007 concerning Limited Liability Companies harmonized with the Civil Code (KUHPer), the Commercial Code (KUHDagang). Law Number 25 of 2007 concerning Investment and Law Number 17 of 2012 concerning Cooperatives, the results of which are contained in Law Number 11 of 2020 concerning Job Creation. Meanwhile, the legal arrangements for individual companies in the future in providing guarantees of legal certainty are regulations related to the statement of the establishment of individual companies as it is known that changes can be made. If traced, there are two categories of changes regulated in PP No. 8/2021, namely changes to the statement of establishment of an individual company and changes to the statement of changes to an individual company.